A Study of the Characteristics of Gaseous and Solid Residues After Coal Dust Explosions. Issue 9 (2nd September 2017) - Liu, Zhentang; Li, Xuelong; Qian, Jifa; Lin, Song; Zhang, Songshan
ABSTRACT: Coal gas and dust explosions greatly affect mine safety. However, our current knowledge of these explosions is primarily based on post-accident investigations and analysis, and thus is insufficient. In the present study, coal dust explosion experiments were carried out in a 20-L spherical vessel, in conjunction with gas chromatography, scanning electron microscopy-energy dispersive X-ray spectroscopy, and industry-standard analyses. In this manner, the characteristics of the gaseous and solid residues generated after explosions were assessed. The results show that the composition of the gaseous products is closely related to the volume fraction, particle size, metamorphism degree, and ignition energy. Significant differences are found in the morphology and industry standard analysis results between the original coal and the solid post-explosion residues. These results provide important data to support theoretical analyses regarding the coal dust explosion process and the analysis of material evidence from explosion sites.